Osler-Weber-Rendu syndrome during pregnancy. (25th June 2013) - Inocêncio, G; Braga, A; Lima, T; Buchner, G
Abstract : Osler-Weber-Rendu syndrome is a very rare systemic fibrovascular dysplasia. Rupture of angiomas can cause haemorrhages, which sometimes can be severe with difficult bleeding control. The main manifestation is recurrent epistaxis. Treatment of this disorder is symptomatic. During pregnancy, there may be an increased risk of complications. We describe a case of a pregnant woman with Osler-Weber-Rendu syndrome. Besides frequent epistaxis and microcytic hypochromic anaemia that resolved with oral iron treatment, she had a normal pregnancy, vaginal delivery and puerperium without complications.